Market Anomalies: January Effect and Weekend Effect on Stock Return - Jannah, Rosidatul; Hidayat, Nur (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Every investor will always expect a return from their investment and can take advantage of seasonal or calendar anomalies to get the expected return. Seasonal or calendar anomalies are measured using the January Effect and Weekend Effect to determine the pattern of stock price movements. This study aims to examine the effect of the January Effect and Weekend Effect on stock returns. The population used is the LQ45 index which consists of 45 companies. The sample used was 17 companies selected through the purposive sampling technique. The data analysis method used is descriptive statistical analysis and multiple linear regression models. The results showed that stock returns in January showed a negative value, indicating that the January Effect did not affect stock returns. Stock returns show a positive value on Friday compared to other trading days which indicates the Weekend Effect has an effect on stock returns. Together, the January Effect and Weekend Effect influence LQ45 stock returns on the IDX. Keywords: January Effect; Weekend Effect; Return; Investment; Public Information